2007
DOI: 10.1080/01926230701338966
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive and Bioenergetic Signaling Effects of PDK1/Akt Pathway Inhibition in a Transgenic Mouse Model of Prostate Cancer

Abstract: The phosphoinositide-dependent kinase 1 (PDK1)/Akt pathway is an important regulator of multiple biological processes including cell growth, survival, and glucose metabolism. In light of the mechanistic link between Akt signaling and prostate tumorigenesis, we evaluated the chemopreventive relevance of inhibiting this pathway in the transgenic adenocarcinoma of the model prostate (TRAMP) mouse with OSU03012, a celecoxib-derived, but COX-2-inactive, PDK1 inhibitor. Beginning at ten weeks of age when prostatic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 46 publications
1
31
1
Order By: Relevance
“…Centrilobular hepatocellular hypertrophy was observed in mice from both groups receiving OSU-03012 treatments. Aside from this change, which we have reported previously (32), no significant lesions were detected in any tissues from animals subjected to histopathologic examination. To correlate these in vivo antitumor effects with mechanisms identified in vitro, intratumoral biomarkers of drug activity were assessed by immunohistochemistry and immunoblotting of tumor homogenates.…”
Section: Cancer Researchmentioning
confidence: 80%
“…Centrilobular hepatocellular hypertrophy was observed in mice from both groups receiving OSU-03012 treatments. Aside from this change, which we have reported previously (32), no significant lesions were detected in any tissues from animals subjected to histopathologic examination. To correlate these in vivo antitumor effects with mechanisms identified in vitro, intratumoral biomarkers of drug activity were assessed by immunohistochemistry and immunoblotting of tumor homogenates.…”
Section: Cancer Researchmentioning
confidence: 80%
“…Treatment was initiated 7 d after injection, with the gavage dose of drug adjusted twice weekly to mirror the dose of drug consumed in the diet. TRAMP mice (C57BL/6TRAMPxFVB) were generated and housed as previously reported (28). The reversibility of observed OSU-HDAC42-associated toxicity was determined in age-matched nontransgenic (wild-type) littermates of TRAMP mice, which included comparison of weights of the adrenal glands, brain, epididymides, epididymal fat pads, heart, kidneys, liver, pituitary gland, spleen, testes, and thymus.…”
Section: Methodsmentioning
confidence: 99%
“…An extended set of tissues from representative animals (n = 3, 5, and 10 for the pharmacodynamic, xenograft, and TRAMP studies, respectively) was evaluated microscopically in accordance with Society of Toxicologic Pathology-proposed guidelines for repeat-dosing toxicity studies (29), with the exception of spinal cord and female reproductive organs. Dorsal (DP), lateral (LP), ventral (VP), and anterior (AP) prostate lobes, iliac lymph nodes, liver (left lobe), and lungs from each TRAMP mouse were collected, fixed, processed, and evaluated as described (28). Testes were fixed for 24 h in Bouin's fixative and then transferred to 70% ethanol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al (21) showed that the loss of mitochondrial membrane potential may be involved in OSU-03012-induced cell death in multiple myeloma cells. Furthermore, genomic inhibition of PDK1 was reported to suppress cardiac functions in the mouse heart (3,8,11), however, severe cardiac side effects of OSU-03012 were not reported at blood concentrations below 20 μM (6,15). To our knowledge, information on direct effects of OSU-03012 on cardiac function is absent.…”
mentioning
confidence: 66%